ADV-Based Investigation on Bed Level Changes Over a Meso-Macro Tidal Beach - Pang, Wenhong; Zhou, Xiaoyan; Dai, Zhijun; Li, Shushi; Huang, Hu; Lei, Yaping (Frontiers in Marine Science, 2021)
Beach intra-tidal bed level changes are of significance to coastal protection amid global climate changes. However, due to the limitation of instruments and the disturbance induced by wave motions superimposed on water levels, it was difficult to detect the high-frequency oscillation of the submerged beach bed level. In this study, an observation, lasting for 12 days and covering the middle tide to the following spring tide, was conducted on a meso-macro tidal beach, Yintan Beach, to simultaneously detect the characteristics and influence mechanism of bed level changes at intra-tidal and tidal cycle scales. The collected data included water depth, suspended sediment concentration (SSC), waves, high-frequency three-dimensional (3-D) velocity, and the distance of the seabed to the acoustic Doppler velocimeter (ADV) probe, which were measured by an optical backscatter sensor, two Tide & Wave Recorder-2050s, and an ADV, respectively. The results showed that the tidal cycle-averaged bed level decreased by 58.8 mm, increased by 12.6 mm, and increased by 28.9 mm during neap, middle, and spring tides in succession, respectively, compared with the preceding tidal regimes. The net erosion mainly resulted from large incident wave heights and the consequent strong offshore-directed sediment transport induced by undertows. Moreover, the variations in the bed level were more prominent during a neap to middle tides than during middle to spring tides, which were jointly caused by the wave-breaking probability regulated by water depth and the relative residence times of shoaling wave, breaker, and surf zones that were determined by relative tidal range. In terms of the intra-tidal bed level, it displayed an intra-tidal tendency of increase during floods and decrease during ebb tides, i.e., the intra-tidal bed level changes were controlled by water depth, which modulated the effects of waves on sediment resuspension and vertical sediment exchange. To be specific, waves and SSC were responsible for the intra-tidal bed level changes under low-energy wave conditions, while mean current and bedform exerted important influences on the variations of the intra-tidal bed level under moderate wave conditions, which broke the foregoing interrelation between bed level, waves, and SSC. This study, therefore, emphasizes the usage of ADV measurement to investigate bed level changes in sandy coasts.